MARKETISATION OF HIGHER EDUCATION IN PAKISTAN: A CRITICAL DISCOURSE ANALYSIS OF THE PAKISTANI UNIVERSITIES’ ADVERTISEMENTS - Muhammad Ibrahim; Syeda Sabira; Nasir Hussain (International Journal of Contemporary Issues in Social Sciences, 2024)
In today’s dynamic educational landscape, universities have shifted their role from centers of learning to corporate institutions. This study focuses on Pakistani universities, delving into the marketization of higher education and investigating the sociocultural impact and discursive strategies in their advertisements during admission drives. The purpose of this study is to reveal how Pakistani universities position themselves in the competitive educational market. Furthermore, it aims to explore the commodification of knowledge by Pakistani universities for financial benefits. Advertisements by universities, both in print and social media, serve as the initial motivation for student admissions. Universities compete for student enrollment by embedding sociocultural norms intertextually and discursively in their advertisements. Previous studies focus on genre analysis techniques to analyze advertisements; however, this study adopts a broader approach towards understanding the marketization of higher education. The study employs a qualitative method by analyzing 30 advertisements, selected through purposive sampling, and utilizes the Fairclough 3D model as the research framework. The analysis reveals that advertisements aimed at attracting prospective students are highly discursive, serving both promotional and informative purposes. Various strategies are employed, foregrounding the history, ranking, buildings, and faculty of the universities by using adjectives and nominals as grammatical choices to project quality and prestige. Furthermore, the appeal to students is enhanced by the quantification of programs, faculty members, and history to demonstrate credibility. Overall, university advertisements create asymmetrical power dynamics, portraying the university as authoritative and students as dependents.